Estimating Time Between Central Line-associated Bloodstream Infection Events. (4th October 2017) - Edwards, Jonathan; Pollock, Daniel
Abstract: Background: Central line-associated bloodstream infection (CLABSI) event data reported by acute care hospitals (ICUs and select ward locations) to CDC's National Healthcare Safety Network (NHSN) since 2015, pursuant to federal reporting requirements, are important data with which to explore basic questions about the applicability of time between events (TBE) monitoring to HAI surveillance. TBE monitoring has had demonstrable value for quality measurement and improvement when applied to successive occurrences of other types of adverse events, particularly outside of healthcare, that have low occurrence rates. However, more needs to be learned about the feasibility, methods, and results of applying TBE monitoring to HAI data to establish whether and how this technique can be put to routine use in HAI surveillance efforts. Methods: TBE data for the 27, 428 CLABSIs reported NHSN in 2016 were used for this analysis. Patient care location types were included if ≥50 CLABSIs were reported. TBE were modeled using the Geometric distribution for several location types and a needle plot was used to determine whether the data are adequately described by this distribution. Estimation of the probability of CLABSI occurring on any given day and probability limits for TBE from the fitted Geometric distribution used for creating t-charts and quality control purposes were compared among location types. Results: Estimates of the probability of a CLABSI occurring among ICU patients on a given day ranged from P = 0.0424 for Medical ICUs to P = 0.0114 for neurologic ICUs. Among surgical, medical/surgical and medical wards the probability was P = 0.0128, 0.0153 and 0.0156 (Figure 1), respectively. T-chart Upper probability limits ranged from 122 days for medical ICUs (Figure 2) to 460 days for neurologic ICUs and ranged from 337 to 411 among the select wards. Conclusion: Estimating the probability that a CLABSI will occur on any given day in a hospital ICU or ward location based entirely on TBE can be useful to determine the expectation of these rare events. Implementation of t-charts with upper and lower probability limits can help hospitals better track CLABSI TBE in their patient care locations and be used to signal prevention progress. Disclosures: All authors: No reported disclosures.